If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + -46 = 4(x + -1) + -3 Combine like terms: 23 + -46 = -23 -23 = 4(x + -1) + -3 Reorder the terms: -23 = 4(-1 + x) + -3 -23 = (-1 * 4 + x * 4) + -3 -23 = (-4 + 4x) + -3 Reorder the terms: -23 = -4 + -3 + 4x Combine like terms: -4 + -3 = -7 -23 = -7 + 4x Solving -23 = -7 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -23 + -4x = -7 + 4x + -4x Combine like terms: 4x + -4x = 0 -23 + -4x = -7 + 0 -23 + -4x = -7 Add '23' to each side of the equation. -23 + 23 + -4x = -7 + 23 Combine like terms: -23 + 23 = 0 0 + -4x = -7 + 23 -4x = -7 + 23 Combine like terms: -7 + 23 = 16 -4x = 16 Divide each side by '-4'. x = -4 Simplifying x = -4
| x+.21x=92000 | | 4+9y-15=2y-11+y | | 3(0.9-t)=-5(16.5+3t) | | 3(0.9-t)=-5(-16.5+3t) | | x+.23x=110000 | | 7(x+1)=5-2(7x+6) | | -8+12y=-10 | | 3-2x=4+2x | | 3(-2)+4=5-6 | | -5(1-2x)=8 | | ln(7x^2-3)=2 | | 10(-3-2t)+10-12t+26=0 | | x-7=7-x | | -7x+4=x | | 0=2x-17 | | 5-9+=6+2-3 | | -7(x+3)-10=31+1 | | -3z-8=10 | | 10x-5x-3=-2 | | 9-8=8 | | 4x^4-12x^3+3=0 | | 5(4x-3)+x=7(3x+2) | | -2y-13=6y+19 | | -8(x-2)+2=58 | | 9y+12y=63 | | 7x=96-x | | -2(11-4c)=11(c-8) | | 9y+7.7=-4.5 | | 8(-2)=16 | | 5y+7=62 | | 4(x+12)-5=79 | | (x-1)(3x-5)(4x-8)=0 |